Overexpression of GmUBC9 Gene Enhances Plant Drought Resistance and Affects Flowering Time via Histone H2B Monoubiquitination - Chen, Kai; Tang, Wen-Si; Zhou, Yong-Bin; Xu, Zhao-Shi; Chen, Jun; Ma, You-Zhi; Chen, Ming; Li, Hai-Yan (Frontiers in Plant Science, 2020)
Ubiquitylation is a form of post-translational modification of proteins that can alter localization, functionality, degradation, or transcriptional activity within a cell. E2 ubiquitin-conjugating enzyme (UBC) and E3 ubiquitin ligases are the primary determinants of substrate specificity in the context of ubiquitin conjugation. Multiubiquitination modifies target proteins for 26S proteasome degradation, while monoubiquitination controls protein activation and localization. At present, research on the monoubiquitination, especially histone monoubiquitination, has mostly focused on model plants with relatively few on crop species. In this study, we identified 91 UBC-like genes in soybean. The chromosomal localization, phylogenetic relationships, gene structures, and putative cis-acting elements were evaluated. Furthermore, the tissue-specific expression patterns of UBC Class I genes under drought stress were also investigated. Among Class I genes, GmUBC9 induction in response to drought stress was evident, and so this gene was selected for further analysis. GmUBC9 localized to the nucleus and endoplasmic reticulum. The overexpression of GmUBC9 in Arabidopsis led to enhanced tolerance for drought conditions across a range of stages of development, while overexpression in soybean hairy roots similarly led to improvements in tolerance for drought conditions, increased proline content, and reduced MDA content in soybean seedlings compared to wild type plants. HISTONE MONOUBIQUITINATION 2 (HUB2), an E3-like protein involved in histone H2B ubiquitylation (H2Bub1), was found to interact with GmUBC9 through Y2H analysis and BiFC assays in Arabidopsis and soybean. Under drought conditions, the level of H2Bub1 increased, and transcription of drought response genes was activated in GmUBC9 transgenic Arabidopsis and soybean. In addition, GmUBC9 transgenic Arabidopsis and soybean showed a late-flowering phenotype and had increased expression levels of the flowering related genes FLC and MAF4. These findings indicate that GmUBC9 is important for drought stress response and regulation of flowering time in soybean.